2005
DOI: 10.1071/wr04089
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the detection of possums by spotlighting in Western Australia

Abstract: This paper describes how environmental factors, survey method procedures and differences in forest structure resulting from logging relate to the detection of koomal (common brushtail possum, Trichosurus vulpecula hypoleucus) and ngwayir (western ringtail possum, Pseudocheirus occidentalis). A total of 169 vehiclebased spotlight surveys of possums within native jarrah (Eucalyptus marginata) forest was conducted on three transects over eight years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003). Up to 5.7 koom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Greater wind speed also decreased the number of common brushtail possums (Trichosurus vulpecula) observed in open pasture (Paterson 1993). Wind speed did not influence the detection rate of P. occidentalis in a forest habitat (Wayne et al 2005); however, the rope bridge in this study was completely exposed to the wind over the road, and strong wind could deter P. occidentalis from crossing the open bridge. Given this information, we also predicted that P. occidentalis would cross the bridge more during their breeding seasons and less on well lit, cold and/or windy nights.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Greater wind speed also decreased the number of common brushtail possums (Trichosurus vulpecula) observed in open pasture (Paterson 1993). Wind speed did not influence the detection rate of P. occidentalis in a forest habitat (Wayne et al 2005); however, the rope bridge in this study was completely exposed to the wind over the road, and strong wind could deter P. occidentalis from crossing the open bridge. Given this information, we also predicted that P. occidentalis would cross the bridge more during their breeding seasons and less on well lit, cold and/or windy nights.…”
Section: Introductionmentioning
confidence: 85%
“…Whether this trend is caused by possums generally reducing their activities on bright nights or possums being discouraged to cross the exposed bridge on brighter nights cannot be known from our data. Wayne et al (2005) reported that the moon or wind had no effect on the number of possums seen by spotlighting in a forest; however, possums are likely to act differently in a completely exposed environment such as on a rope bridge compared to an environment with greater cover from predators such as the canopy in a forest. Native owl species, such as the masked owl (Tyto novaehollandiae) are thought to be present in the region (Clarke 2011), and they prey on similar sized possum species in New South Wales (Kavanagh 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18 spotlight nights were generally conducted once per week. To limit environmental effects on the detection efficiency (Davey 1990;Laurance 1990;Wayne et al 2005), spotlighting was not conducted on evenings of extreme or inclement weather.…”
Section: Spotlight Methods Trialsmentioning
confidence: 99%
“…Extensive monitoring programs are conducted using population indices by assuming that the probability of detection is constant over space and time (Pollock et al 2002), which is clearly invalid in many field studies (Yoccoz et al 2001;Pollock et al 2002). Species detectability can be influenced by environmental variables, habitat features and observer bias (Bayliss 1987;Lancia et al 1996;Karanth et al 2003;Field et al 2005;Wayne et al 2005;Pinto et al 2006). These problems are generally underestimated by wildlife biologists in vertebrate surveys (Yoccoz et al 2001;Pollock et al 2002).…”
Section: Introductionmentioning
confidence: 99%